Marvelous and the black hole [videorecording (DVD)] - Cech, Miya, 2007-; Perlman, Rhea; Nam, Leonardo; Lule, Paulina; Omachi, Kannon; Park, Jae Suh; Slavin, Jonathan (FilmRise, 2022)
A teenage delinquent befriends a surly magician who helps her navigate her inner demons and dysfunctional family with sleight of hand magic. A coming-of-age comedy that touches on unlikely friendships, grief and finding hope in the darkest moments.